Importancia de la ética en la educación - Velaochaga Sacio, Ramiro (2018)
The education has always represented a fundamental factor for human development. This article highlights the present importance of education in confronting an increasingly globalized and competitive world, and the efforts that the educational systems make to implement methods and infrastructures aimed at providing students with the abilities to achieve meaningful learning skills. However, it is alarming that these educational systems have neglected the moral education of the people, that is, the develop of a solid formation in human values based on ethics that orientates the positive use of freedom as fundamental elements to the process of socialization, personal and integral realization and finally the development of a society based on mutual human respect.